2D Nanomaterials: General and Scalable Solid‐State Synthesis of 2D MPS3 (M = Fe, Co, Ni) Nanosheets and Tuning Their Li/Na Storage Properties (Small Methods 12/2017). Issue 12 (7th December 2017) - Liang, Qinghua; Zheng, Yun; Du, Chengfeng; Luo, Yubo; Zhang, Jianli; Li, Bing; Zong, Yun; Yan, Qingyu
Abstract : In article number1700304, Qingyu Yan and co‐workers develop a general method for the scalable preparation of 2D ternary layered MPS3 (M = Fe, Co, Ni) nanosheets and use them for high‐performance lithium and sodium storage. Their intrinsic compositions and layered nanostructures account for the superior Li/Na storage. Such ternary 2D nanomaterials are also promising for electronics and catalysis applications.